Mathematical Discrete-Time Model of the Heterogeneous Integrated System of Corporate Information Management - Kravets, Oleg Ja (Journal of Siberian Federal University. Mathematics & Physics, 2019)
The article considers some problems and peculiarities of the modelling and rational design of heteroge- neous traffic servicing integrated systems. The aim of this paper is to develop the apparatus of modelling for distributed systems with a heterogeneous medium as part of a subsystem of managing the modelling and upgrading of the systems in question. The research subject is a system consisting of air and cable multiple-access systems. Protocol functions of every level are represented by a double-phase stochastic system within discrete time. Results of numerical experiments which were obtained in areas of high loads and over-loads allow us to determine possibilities for further prospective expansion of the system and to develop guidelines as to permissible values of system parameters for systems that are functioning in different modes. The obtained results can be used for the reconfiguration of both static and dynamic heterogeneous (according to the transmission medium) information systems